(untitled) (Research, Society and Development, 2024)
Introduction: Implantodontia is intended to replace missing teeth through the placement of dental implants, as advances in the area make it possible to observe a variety of methods and materials, among them, as well as zirconia ceramics with the same success characteristics in area. Objective: to analyze and highlight the benefits and advantages of using zirconia dental implants in rehabilitative clinical dentistry. Methodology: This work consisted of a literature review based on articles published in the databases Biblioteca Virtual em Saúde, Scientific Electronic Library Online and PubMed guided by Describers in Ciências da Saúde: Zirconia, Benefits, Implant, Rehabilitation, period from 2019 to 2024. Results: According to the eligibility criteria, 2757 foram articles were found, after triagem of literature, 11 foram articles were included and several data were described and discussed through syntheses. Conclusion: It is concluded that zirconia implants offer notable benefits in implant-supported rehabilitation, highlighting excellent aesthetics and high biocompatibility.